2019
DOI: 10.1177/2057150x19872742
|View full text |Cite
|
Sign up to set email alerts
|

The psychology of peasant religious conversion for the purpose of disease control: The role of belief in understanding Chinese rural religious practices

Abstract: This paper focuses on the religious psychology of peasants who undergo religious conversion in order to cure an illness or disease. Field research was conducted in Wang village in Northern Jiangsu, examining the psychology of newly converted peasants. In academic circles psychology of peasants is usually critiqued according to utility and rationality. In this paper, belief is a starting point for understanding the psychology of peasants. The natural mentality and family ethics of the peasants lead them to plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Cognitive process traditionally refers to the process of understanding, which is a psychological process in which the human brain reflects on the characteristics and relationships of objective things in the form of perception, memory, and thinking [49]. Ching et al [50] defined green consumption cognition as consumers' views and level of understanding with regards to environmental protection concepts as evidenced by surroundings, facilities, and service and hypothesized that consumers' green consumption cognition would affect their behavioral intention.…”
Section: The Influence Of Green Consumption Cognition On Consumer Pur...mentioning
confidence: 99%
“…Cognitive process traditionally refers to the process of understanding, which is a psychological process in which the human brain reflects on the characteristics and relationships of objective things in the form of perception, memory, and thinking [49]. Ching et al [50] defined green consumption cognition as consumers' views and level of understanding with regards to environmental protection concepts as evidenced by surroundings, facilities, and service and hypothesized that consumers' green consumption cognition would affect their behavioral intention.…”
Section: The Influence Of Green Consumption Cognition On Consumer Pur...mentioning
confidence: 99%
“…This is further reinforced by the utilitarian nature of Chinese faith. Relevant empirical studies have shown that one of the most important reasons why Chinese people believe in religion is because either they or their family members are sick (Zhou and Sun 2017).…”
Section: Integrated Analytical Frameworkmentioning
confidence: 99%
“…The percentage of people claiming some type of religious practice was 7% in 2001, it then rose to 10% in 2012, and 26.4% in 2014 (Lu and Zhang 2016;Wenzel-Teuber 2017). Some residents in China seek help from religion due to social stresses, or the burden of chronic diseases of themselves or family members (Liang and Qi 2015;Zheng and Wang 2014;Zhou and Sun 2017).…”
Section: Religion Background In Chinamentioning
confidence: 99%